Mitochondrial DNA abnormalities and metabolic syndrome - Ding, Xudong; Fang, Tingting; Pang, Xiaoqi; Pan, Xueru; Tong, Aiying; Lin, Ziyi; Zheng, Shikuan; Zheng, Ningning (Frontiers in Cell and Developmental Biology, 2023)
Metabolic syndrome (Mets) refers to the pathological state of carbohydrate, protein, fat and other substances in the human body, which is a risk factor leading to diabetes, cardiovascular and cerebrovascular diseases. The pathogenesis of the metabolic syndrome is not yet clear, but is currently thought to be the result of mitochondrial dysfunction, closely related to the mitochondrial genome, proteome and mitochondrial dynamics. Studies have shown that reduced mitochondrial DNA copy number and gene mutations, abnormalities in mitochondrial DNA-encoded proteins, mitochondrial proteases and imbalances in mitochondrial dynamics not only contribute to mitochondrial dysfunction, but also participate in the development of metabolic syndrome. Therefore, promoting the restoration of mitochondrial function by recovering the above defects may become a new strategy for the treatment of metabolic syndrome. This paper mainly reviews the research progress and significance of mitochondrial genome, proteome and mitochondrial dynamics in metabolic syndrome, in order to provide a theoretical basis for reducing the occurrence of diabetes mellitus and cardiovascular and cerebrovascular diseases.